Analisis Pengaruh Tingkat Pendidikan Formal Dan Motivasi Terhadap Kepuasan Kerja Karyawan Universitas Muhammadiyah Yogyakarta Dengan Gender Sebagai Variabel Moderasi - Hidayat, Wahyu (208-7721)
This study discusses the effect formal education and motivation on Job satisfaction employee in the Muhammadiyah University of Yogyakarta with gender as the variable Moderation          The subjects were regular employees Muhammadiyah University of Yogyakarta with a sample of 152 people. Data were collected survey method is to gives a list of questions or questionnaires directly to the respondents. Technique of analyzing data used in this research was the phased linear regression, analysis the testing effect between variable level of formal education and motivation to variable job satisfaction conducted by multiple regression analysis (multiple regression). While for the testing variable level of formal education and motivation on job satisfaction variable with a view the interaction effects of gender as a moderating variable using Moderated regression analysis (MRA), which is operated by IBMs SPSS version 21.          Results of research show that the, level of formal education and motivation significant and positive impact on job satisfaction, level of  formal education and a significant positive effect on job satisfaction, motivation and a positive significant effect on job satisfaction, and motivation level of formal education with gender as a moderating variable affects the job satisfaction.